2014
DOI: 10.1007/978-1-4939-1872-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Urine Sample Preparation and Fractionation for Global Proteome Profiling by LC-MS

Abstract: Urine has garnered tremendous interest over the past decade as a potential source of protein biomarkers for various pathologies. However, due to its low protein concentration and the presence of interfering compounds, urine constitutes a challenging analyte in proteomics. In the context of a project aimed at the discovery and evaluation of new candidate biomarkers of bladder cancer in urine, our laboratory has implemented and evaluated an array of preparation techniques for urinary proteome analysis. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Thus, while being perhaps the ideal matrix in terms of clinical diagnoses, it is one of the worst-case scenarios in terms of measurement science. 12 Because of the challenges in protein monitoring and analysis due to the complexity of samples, 13,14 a separation step or multiple steps are standard practice in proteomics. 15,16 Current methods include solid phase extraction (SPE), 2D gels, ligand binding assays, precipitation steps and ltration steps.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while being perhaps the ideal matrix in terms of clinical diagnoses, it is one of the worst-case scenarios in terms of measurement science. 12 Because of the challenges in protein monitoring and analysis due to the complexity of samples, 13,14 a separation step or multiple steps are standard practice in proteomics. 15,16 Current methods include solid phase extraction (SPE), 2D gels, ligand binding assays, precipitation steps and ltration steps.…”
Section: Introductionmentioning
confidence: 99%
“…We could not obtain data for long-term use of this new method for in terms of device maintenance, repair and consumption costs. However, it can be determined in more comprehensive studies can be conducted to see whether the LC-MS/MS device will reduce the maintenance costs or not (4,(8)(9)(10)(11). In this study, we showed that a simple but time-consuming urine preparation method for the first time in urine preparation did not influence the results.…”
Section: Discussionmentioning
confidence: 69%
“…Diversities of urine samples in gender, age, and ethnicities should be considered in future studies. Additionally, while our workflow is a good compromise between throughput and the depth of the urine proteome, it would be more useful to automate the system, decrease sample preparation time, adopt a gel-free method and further increase sample throughput (Court et al, 2015, Santucci et al, 2015, Yu et al, 2014). …”
Section: Discussionmentioning
confidence: 99%